Aurora kinase A is essential for meiosis in mouse oocytes - Blengini, Cecilia S; Ibrahimian, Patricia; Vaskovicova, Michaela; Drutovic, David; Solc, Petr; Schindler, Karen (PLoS genetics, 2021)
The Aurora protein kinases are well-established regulators of spindle building and chromosome segregation in mitotic and meiotic cells. In mouse oocytes, there is significant Aurora kinase A (AURKA) compensatory abilities when the other Aurora kinase homologs are deleted. Whether the other homologs, AURKB or AURKC can compensate for loss of AURKA is not known. Using a conditional mouse oocyte knockout model, we demonstrate that this compensation is not reciprocal because female oocyte-specific knockout mice are sterile, and their oocytes fail to complete meiosis I. In determining AURKA-specific functions, we demonstrate that its first meiotic requirement is to activate Polo-like kinase 1 at acentriolar microtubule organizing centers (aMTOCs; meiotic spindle poles). This activation induces fragmentation of the aMTOCs, a step essential for building a bipolar spindle. We also show that AURKA is required for regulating localization of TACC3, another protein required for spindle building. We conclude that AURKA has multiple functions essential to completing MI that are distinct from AURKB and AURKC.
Keywords: póly dělícího vřeténka; aparát dělícího vřeténka; Microtubule-Associated Proteins; polo-like kinasa 1; protein-serin-threoninkinasy; oocyty; vývojová regulace genové exprese; fetální proteiny; dělení bunečného jádra; Protein Serine-Threonine Kinases; Gene Expression Regulation, Developmental; Spindle Apparatus; Proto-Oncogene Proteins; Polo-Like Kinase 1; Aurora Kinase B; proteiny asociované s mikrotubuly; Meiosis; Microtubule-Organizing Center; proteiny buněčného cyklu; meióza; segregace chromozomů; Animals; Aurora kinasa A; lidé; Aurora Kinase A; ženské pohlaví; Cell Nucleus Division; Humans; zvířata; Aurora kinasa C; myši; Aurora Kinase C; Fetal Proteins; Spindle Poles; Aurora kinasa B; Chromosome Segregation; Mice; Female; Cell Cycle Proteins; organizační centrum mikrotubulů; protoonkogenní proteiny; Oocytes